EDI SUROJO MEDIA PENGENALAN KEBUDAYAAN LOKAL BERBASIS KARAKTER UNTUK ANAK USIA DINI - Fatimah Noor Isnaini (Jurnal Pendidikan Anak, 2018)
AbstractBased on interviews with some teachers that introducing puppet and puppet story is very important for early childhood because it introduced wayang stories that give good values that can be imulated by young children.  But now, the puppet is not widely known. Research shows that teachers and principals from kindergarten yet have the ability to develop materials and instructional media about puppets kindergarten teachers and a lack of understanding about the puppet. Therefore, the media should be designed to introduce about puppet in early childhood. The author makes an Edi Surojo (Ensiklopedia Superhero Jowo) Three Dimensions as Media Recognition Based Local Culture Character For Early Childhood. The research methods that used for this program is a series of stages that are arranged systematically, the following steps are performed: Preparation general, content creation, design and manufacture. Media such as the Ensiklopedia Superhero Jowo is expected to be an alternative to introducing the local culture in early childhood and develop the values of character education through puppet. Continuous Potential of Ensiklopedia Superhero Jowo are becoming media for introducing the local culture in Indonesia. Ensiklopedia Superhero Jowo can facilitate teachers to introducing the local culture-based character in early childhood.Keywords: character education, puppet, javanesse superhero,  early childhood